A comparative analysis of role attainment and impairment in binge-eating disorder and bulimia nervosa: results from the WHO World Mental Health Surveys. (March 2014) - Kessler, R.C.; Shahly, V.; Hudson, J.I.; Supina, D.; Berglund, P.A.; Chiu, W.T.; Gruber, M.; Aguilar-Gaxiola, S.; Alonso, J.; Andrade, L.H.; Benjet, C.; Bruffaerts, R.; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Background. Cross-national population data from the WHO World Mental Health surveys are used to compare role attainments and role impairments associated with binge-eating disorder (BED) and bulimia nervosa (BN). Methods. Community surveys assessed 23 000 adults across 12 countries for BED, BN and ten other DSM-IV mental disorders using the WHO Composite International Diagnostic Interview. Age-of-onset was assessed retrospectively. Ten physical disorders were assessed using standard conditions checklists. Analyses examined reciprocal time-lagged associations of eating disorders (EDs) with education, associations of early-onset (i.e., prior to completing education) EDs with subsequent adult role attainments and cross-sectional associations of current EDs with days of role impairment. Results. BED and BN predicted significantly increased education (females). Student status predicted increased risk of subsequent BED and BN (females). Early-onset BED predicted reduced odds of current (at time of interview) marriage (females) and reduced odds of current employment (males). Early-onset BN predicted increased odds of current work disability (females and males). Current BED and BN were both associated with significantly increased days of role impairment (females and males). Significant BED and BN effects on adult role attainments and impairments were explained by controls for comorbid disorders. Conclusions. Effects of BED on role attainments and impairments are comparable with those of BN. The most plausible interpretation of the fact that these associations are explained by comorbid disorders is that causal effects of EDs are mediated through secondary disorders. Controlled treatment effectiveness studies are needed to trace out long-term effects of BED–BN on secondary disorders.